Safety and Effectiveness of Pharmacologic Conversion of Atrial Fibrillation and Flutter: Results of Multicenter Trial. Part II: Assessment of Safety - N. Yu. Mironov; Yu. A. Yuricheva; V. V. Vlodzyanovskiy; S. F. Sokolov; Kh. M. Dzaurova; S. P. Golitsyn; Yu. V. Shubik; M. V. Berman; M. M. Medvedev; A. E. Rivin; D. S. Parkhomchuk; A. E. Barybin; et al. (Рациональная фармакотерапия в кардиологии, 2021)
Aim. We aimed to assess safety and effectiveness of class III antiarrhythmic drug Refralon for conversion of atrial fibrillation (AFib) and flutter (AFl) in post-registration trial and to compare data of primary center (National medical research center in cardiology) with data of other hospitals.Material and Methods. We performed retrospective cohort study in 727 patients (451 enrolled in primary center and 276 enrolled in other hospitals) admitted between June 24, 2014 and June 24, 2019. Refralon was administered for conversion of AFib and AFl in intense care units in escalating doses (10-30 micrograms/kg) intravenously.Results. Conversion of AFib and AFl into sinus rhythm was achieved in 53,6% after administration of 10 mcg/kg dose, in 73% after administration of 20 mcg/kg dose and in 91,6% after administration of Refralon in dose up to 30 mcg/kg. No mortality and no major adverse cardiac events registered in our study. Asystole >3.0 sec observed in 5% (35 of 727) of patients): in 5% (24 of 451) of patients enrolled in primary center and in 4% (11 of 276) of patients enrolled in other hospitals; 95% confidence interval (CI) [-0.09; 0.113]. Asystole> 5.0 s observed in 1.7% of patients who further required non-urgent implantation of a permanent pacemaker due to manifestations of sinus node dysfunction. Cardiac conduction disturbances (exclusively sinus bradycardia) were registered in 7% (53 of 727) patients: in 8% (37 of 451) of patients enrolled in primary center and in 6% (17 of 276) of patients enrolled in other hospitals; 95% CI: [-0.1; 0.15]. Only 0.14% of patients had symptomatic sinus bradycardia that resolved after atropine injection. Ventricular arrhythmias (exclusively Torsade de pointes tachycardia in excessive QT interval prolongation) were registered in 1.7% (12 of 727) patients: in 2% (9 of 451) of patients in primary center and in 1% (3 of 276) of patients of other hospitals; 95% CI: [-0.06; 0.08]. QTc interval prolongation to values >500 ms documented in 19% (138 of 727) of patients: in 21% (95 of 451) of patients in primary center and in 16% (43 of 276) of patients in other hospitals; 95% CI: [-0.13; 0.24].Conclusion: In post-registration multicenter trial Refralon demonstrated good safety profile in conversion of AFib and AFl. Potential risk of TdP tachycardia mandates precautions with the use of the drug. In other hospitals Refralon did not demonstrate lower safety than in primary medical center.